Synthesis of Magnolignan, a New Pigment Lightening Component, via a Suzuki-Miyaura Reaction - Shuhei Narita; Tetsuhiro Ogura; Toyonobu Usuki (Journal of Chemistry)
Magnolignan, 2,2′-dihydroxy-5,5′-dipropyl-biphenyl (1), is a down-regulator of melanin synthesis that inhibits the maturation of tyrosinase. In this study, a concise total synthesis of 1 was achieved in five steps with 50% overall yield starting from commercially available trans-anethole (2) via a Suzuki-Miyaura reaction.